2011
DOI: 10.4049/jimmunol.1001505
|View full text |Cite
|
Sign up to set email alerts
|

A Major Role for Bim in Regulatory T Cell Homeostasis

Abstract: We have previously shown that regulatory T cells (Treg) accumulate dramatically in aged animals and negatively impact the ability to control persistent infection. However, the mechanism(s) underlying the age-dependent accrual of Treg remain unclear. Here, we show that Treg accumulation with age is progressive and likely not the result of increased thymic output, increased peripheral proliferation, nor from enhanced peripheral conversion. Instead, we found that Treg from aged mice are more resistant to apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(161 citation statements)
references
References 55 publications
9
150
0
2
Order By: Relevance
“…Bim -/-mice provide a model of enhanced susceptibility to autoimmune disease due to the failure to delete effector T cells in the thymus. Additionally, Bim -/-mice have enhanced T reg numbers with time due to a protection from apoptosis of T regs with Bim deficiency [26,[37][38][39]. This study showed that Bim -/-mice maintained normal kidney function and normal kidney histology at 2 months of age, but gradually developed chronic kidney disease with significantly heavier proteinuria and higher serum creatinine.…”
Section: Cd25mentioning
confidence: 73%
See 1 more Smart Citation
“…Bim -/-mice provide a model of enhanced susceptibility to autoimmune disease due to the failure to delete effector T cells in the thymus. Additionally, Bim -/-mice have enhanced T reg numbers with time due to a protection from apoptosis of T regs with Bim deficiency [26,[37][38][39]. This study showed that Bim -/-mice maintained normal kidney function and normal kidney histology at 2 months of age, but gradually developed chronic kidney disease with significantly heavier proteinuria and higher serum creatinine.…”
Section: Cd25mentioning
confidence: 73%
“…T regs accumulate in aged animals and, with low expression of Bim, impact negatively the ability to control persistent infection [37,38,46]. In addition, T regs proliferate under IL-2 stimulation through elevation of anti-apoptotic regulators and inhibition of pro-apoptotic Bim [47][48][49].…”
Section: Cd25mentioning
confidence: 99%
“…Логично было бы предположить, что сразу после рождения субпопуляция Treg представлена в ос-новном тимическими Treg, а в старости, напро-тив -iTreg. Тем не менее на мышах было показа-но, что у старых животных, напротив, отмечается повышение nTreg и снижение уровня iTreg [10]. К сожалению, мнение о том, что мыши являются хорошей моделью для изучения возрастных из-менений в иммунной системе, не подтвердилось.…”
Section: таблица 1 состав основных субпопуляций т-лимфоцитов в перифunclassified
“…(81). T cells from hyperlipidemic mice expressed significantly lower levels of the proapoptotic molecule Bim, which has previously been implicated in Treg function, compared with normal mice (82). Changes in Tregs in hyperlipidemic mice also affected tolerance induction based on approaches that require Tregs, such as costimulatory molecule blockade.…”
Section: R E V I E W S E R I E S : T R a N S P L A N Tat I O Nmentioning
confidence: 99%